2015
DOI: 10.1002/adsc.201400801
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Direct Construction of Sulfonamides via Iodine‐ Mediated Coupling Reaction of Sodium Sulfinates and Amines at Room Temperature

Abstract: A simple, practical, and metal‐free protocol has been developed for the synthesis of sulfonamides from sodium sulfinates and various amines through an iodine‐mediated SN bond formation reaction at room temperature. This green reaction is cost‐effective, operationally straightforward, and especially proceeds under very mild conditions to afford the target products in good to excellent yields (up to 98%).magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…In 2015, the metal-free synthesis of sulfonamides was carried out using the molecular iodine-mediated coupling of various amines with sodium sulfinates at room temperature. The Wang 59 and Song 60 groups independently reported using a stoichiometric amount of iodine for the formation of series of sulfonamides in good to excellent yields ( Table 3 ). Both methods established the sulfonylation using a wide range of primary and secondary amines, including substituted aromatic, aliphatic, acyclic, and cyclic amines.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…In 2015, the metal-free synthesis of sulfonamides was carried out using the molecular iodine-mediated coupling of various amines with sodium sulfinates at room temperature. The Wang 59 and Song 60 groups independently reported using a stoichiometric amount of iodine for the formation of series of sulfonamides in good to excellent yields ( Table 3 ). Both methods established the sulfonylation using a wide range of primary and secondary amines, including substituted aromatic, aliphatic, acyclic, and cyclic amines.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…5, 133.1, 129.4 (2C), 129.2 (2C), 127.3 (2C), 125. 5, 121.8 (2C); IR (ATR): " = 3204, 1302, 1151, 723 cm -1 ; MS (70 eV, EI): m/z (%): 234 (M + +1, 12%), 233 (M + , 86), 168 (40), 141 (24), 93 (12), 92 (100), 77 (51), 65 (33).…”
Section: Characterization Datamentioning
confidence: 99%
“…As a consequence, a depression of the melting point of the mixture is observed. 12 Since its discovery, hundreds of mixtures have been found to form a eutectic phase, with more than ten million low-transition-temperature mixtures being available. 13 Changing one of the DES components can modify dramatically its properties.…”
Section: Introductionmentioning
confidence: 99%
“…b), enter into this reaction, resulting in sulfonamides 3 with good yields. Later it was shown that this transformation could be carried out with use of iodine without external oxidants …”
Section: Synthesis Of Sulfonamidesmentioning
confidence: 99%